II-20 Relevance of mouse lupus models of lupus nephritis to progression of CKD. (31st August 2016) - Berthier, Celine C; Ketzler, Matthias; Davidson, Anne
Abstract : Background: Lupus nephritis progresses to chronic kidney disease (CKD) in an unacceptably high proportion of affected individuals. It is difficult to predict who is at risk for this complication and may therefore need more intensive therapy. Risk for progression of CKD in humans is associated with an interstitial molecular signature containing 68 genes (Ju W et al, Sci Transl Med, 2015). Of these, a decrease in renal expression of EGF with a concomitant increase in urinary EGF improves the ability to predict CKD expression. Materials and methods: To determine whether these 68 genes can be used in pre-clinical studies to model disease and therapeutic responses, we analysed microarray data of kidneys from three mouse lupus strains at various disease stages and after remission induction. Renal macrophage gene expression was assessed using RNASeq. Results: 64/68 genes have mouse gene IDs and 61/64 are represented on the mouse microarray chip. Of these 49 (80.3%) were regulated in the same direction as in humans in at least one strain (38 in NZM2410 mice, 44 in NZW/BXSB mice, 33 in NZB/W mice and 28 common to all three strains). Few genes were unique to a single strain: of these, collagen genes were uniquely expressed in nephritic NZW/BXSB mice. To determine which genes could distinguish early from established disease we compared the profiles of newly proteinuric NZB/W mice to those of NZB/W mice with established disease. 9 genes, including EGF and TIMP1 only became abnormally regulated during established disease, confirming their association with CKD progression. Most of the CKD associated genes normalised after immunosuppression but tended to drift back to their abnormal values during impending relapse. Some of the abnormally regulated genes are derived from macrophages/DCs. Using RNASeq analysis of isolated renal macrophages from NZB/W mice we showed that macrophage restricted C1qa has a similarly high expression level in young and nephritic renal macrophages. Therefore the increased renal expression of this gene can be used as a biomarker of increased macrophage infiltration, a known poor prognostic feature in human lupus nephritis. Conclusions: Mice with lupus nephritis have a strikingly similar pattern of CKD-related gene expression to humans and these genes can be used to track therapeutic responses. Downregulation of EGF and upregulation of TIMP1 are markers of progressive disease in mice as in humans and C1qa can be used as a marker of macrophage infiltration. The fibrosis signature is best modelled in NZW/BXSB mice.